2021
DOI: 10.1128/jvi.01249-21
|View full text |Cite
|
Sign up to set email alerts
|

Structural Study of Aavrh.10 Receptor and Antibody Interactions

Abstract: Recombinant Adeno-associated virus (rAAV) vectors are one of the leading tools for the delivery of therapeutic genes in human gene therapy applications. For a successful transfer of their payload, the AAV vectors have to circumvent potential pre-existing neutralizing host antibodies and bind to the receptor of the target cells. Both these aspects have not been structurally analyzed for AAVrh.10. Here, cryo-electron microscopy (cryo-EM) and three-dimensional image reconstruction were used to map the binding sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…Five amino acid residues (N470, D271, N272, Y446, and W503) that form a pocket at the base of the three-fold axis of symmetry are key to AAV9–galactose binding and tropism [ 115 , 116 ]. Finally, AAVrh.10 has been shown to bind to sulfated N -acetyllactosamine (LacNAc), a glycan with terminal galactose, via a pocket located on the three-fold capsid protrusions [ 118 , 132 ].…”
Section: Transduction Mechanisms Of Natural Aav Serotypesmentioning
confidence: 99%
“…Five amino acid residues (N470, D271, N272, Y446, and W503) that form a pocket at the base of the three-fold axis of symmetry are key to AAV9–galactose binding and tropism [ 115 , 116 ]. Finally, AAVrh.10 has been shown to bind to sulfated N -acetyllactosamine (LacNAc), a glycan with terminal galactose, via a pocket located on the three-fold capsid protrusions [ 118 , 132 ].…”
Section: Transduction Mechanisms Of Natural Aav Serotypesmentioning
confidence: 99%
“…These engineered capsids will not prevent future immune responses upon vector administration but will expand the patient cohort treatable with AAV vectors that previously were precluded due to their pre-existing antibodies. In the past 12 years, the antibody responses against the AAV capsids were primarily simulated with mouse mAbs 13,20,33,34 . However, our recent study characterizing 21 anti-AAV9 capsid mAbs from human patients indicated that human and mouse antibodies may exhibit differential binding characteristics to the AAV capsids 24 .…”
Section: Discussionmentioning
confidence: 99%
“…The visualization of asymmetric features in otherwise icosahedral structures, such as the Fabs binding near or at the capsids' icosahedral symmetry axes, using traditional cryo-EM reconstruction procedures has been challenging as their information is lost due to averaging of the particle. However, standard asymmetric reconstruction is unfeasible here as the Fab binding modes are independent at each axis resulting in a vast number of structural classes (~3 20 possible permutations for the 3-fold binder) 26 . Thus, the localized reconstruction method was used in combination with symmetry relaxation to structurally characterize the 2-, 3-, or 5-fold region to reconstruct the Fabs not conforming to the icosahedral symmetry of the capsid [25][26][27] .…”
Section: Localized Reconstruction Resolves Fabs Bound Close To the Sy...mentioning
confidence: 99%
See 2 more Smart Citations